2010
DOI: 10.1097/id.0b013e3181df1406
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Histomorphometric Analysis of Maxillary Sinus Augmentation With and Without Bone Grafting in Rabbit

Abstract: New bone formation in the experimental group was faster and denser than that in the control group. Replaceable bony window, as an autologous barrier, accelerates new bone formation early in the healing phase compared with the collagen membrane over a bone graft in the maxillary sinus. The replaceable bony window and elevated sinus membrane revealed osteoinductive potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 20 publications
1
48
1
3
Order By: Relevance
“…In humans with maxillary atrophy a widely used technique in connection with dental replacement is maxillary sinus augmentation (Stübinger and Dard, 2013). With this technique, a new compartment is created between the floor of the maxillary sinus and the elevated sinus membrane, and new bone is allowed to be formed (Sohn et al, 2010). This is needed for fixation of titan implants in the maxilla when bone is scarce.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…In humans with maxillary atrophy a widely used technique in connection with dental replacement is maxillary sinus augmentation (Stübinger and Dard, 2013). With this technique, a new compartment is created between the floor of the maxillary sinus and the elevated sinus membrane, and new bone is allowed to be formed (Sohn et al, 2010). This is needed for fixation of titan implants in the maxilla when bone is scarce.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Estudios en animales sugieren que el hueso bovino desproteinizado es reabsorbido y sustituido gradualmente por tejido óseo viable. Es un proceso lento comparándolo con autoinjertos (4) , lo que permite la conservación de la macroestructura reconstruida durante todo el proceso de sustitución. Dependiendo de la disponibilidad ósea (en altura y ancho) en la zona maxilar posterior las opciones para colocar implantes en el lugar correcto son:…”
Section: Introductionunclassified
“…Studies conducted on animals suggest that deproteinized bovine bone is resorbed and gradually replaced by viable bone tissue. It is a slow process compared with autografts (4) , which helps preserve the macrostructure rebuilt in the replacement process. Depending on bone availability (height and width) in the posterior maxillary area, the options for placing implants in the right place are:…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] However some studies reported new bone formation in animal and human's sinus with membrane elevation alone, resorbable gelatin sponge alone, venous blood alone and autologous fibrin gel with concentrated growth factors alone as alternatives to bone materials. [18][19][20][21][22][23][24][25] According to these studies, bone substitutes may not be a prerequisite for sinus augmentation. The function of elevated sinus membrane is controversial, but some studies reported that sinus membrane acted as periosteum and showed osteoinductive potetnial.…”
Section: Sinus Augmentation Using Lateral Window Approachmentioning
confidence: 99%